EFEKTIVITAS PENERAPAN STRATEGI PEMBELAJARAN START WITH A QUESTION PADA PEMBELAJARAN IPS EKONOMI TERHADAP KECAKAPAN BERFIKIR SISWA KELAS VIII SMP - Dila, Sandi; Hamka, Hamka; Yusuf, Yusuf (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to determine the effectiveness of the application of the Start with A Question learning strategy in the Social Studies learning of Economics on the Thinking Skills of Class VIII Students of SMP Negeri 1 Mare, Mare District, Bone Regency. The benefit of research is to help students solve problems by using Start with A Question learning. This type of research is quantitative research, with the total population in this study is 57 people consisting of male 28 students and 29 female students, using the total sample. To find effectiveness, the experimental class was used, namely VIII A as many as 28 and the control class VIII B as many as 29 people. Data collection techniques used: 1) a questionnaire to Start with A Question; 2) documentation for the social studies learning outcomes. Meanwhile, the data analysis technique used inferential statistics. The results showed the value of t count in pretest=4,942 and posttest=10,253 at a significant level of 5 percent=2,000 and 1 percent=2,660 where degrees of freedom (db)=55. If r count is greater than r table, then the hypothesis is nil (H0) rejectef and the alternative hypothesis (H1) is accepted, namely: “Application of the Start with A Question Learning Strategy in Economic Social Studies Learning to Thinking Skills of Class VIII Syudents of SMP Negeri 1 Mare, Mare District, Bone Regency.